Regular insulin, rather than rapid‐acting insulin, is a suitable choice for premeal bolus insulin in lean patients with type 2 diabetes mellitus. Issue 1 (21st August 2012) - Kuroda, Akio; Kaneto, Hideaki; Kawashima, Satoshi; Sakamoto, Kenya; Takahara, Mitsuyoshi; Shiraiwa, Toshihiko; Yasuda, Tetsuyuki; Katakami, Naoto; Matsuoka, Taka‐aki; Shimomura, Iichiro; Matsuhisa, Munehide
Abstract: The aim of the present study was to compare the usefulness of premeal rapid‐acting and regular insulin in type 2 diabetes patients. A total of 56 type 2 diabetic patients were investigated during hospitalization. Premeal rapid‐acting insulin was applied instead of other medications. Premeal insulin was titrated to adjust premeal and bedtime blood glucose levels to 81–120 mg/dL. Premeal rapid‐acting insulin was changed to regular insulin just before a meal at the same dosage if the postmeal blood glucose level was lower than the premeal blood glucose level. A total of 15 patients changed to regular insulin, and 41 patients continued rapid‐acting insulin. The blood glucose level was comparable between these two groups. Body mass index was significantly lower in the patients using regular insulin. According to the multivariate logistic regression analysis, low body mass index was an independent variable accounting for the usefulness of regular insulin. Regular insulin, rather than rapid‐acting insulin, is a suitable choice for premeal insulin in lean type 2 diabetic patients.